2003
DOI: 10.1074/jbc.m305227200
|View full text |Cite
|
Sign up to set email alerts
|

Scapinin, a Putative Protein Phosphatase-1 Regulatory Subunit Associated with the Nuclear Nonchromatin Structure

Abstract: It is thought that the nuclear nonchromatin structures, such as the nuclear matrix and lamina, play regulatory roles in gene expression. In this study, we identified an insoluble protein that was associated with the chromatin-depleted nuclear structure of proliferating human leukemia HL-60 cells. Preparation of the chromatin-depleted nuclear structure, referred to as the nuclear matrix-intermediate filament scaffold (Fey, E., Krochmalnic, G., and Penman, S. (1986) J. Cell. Biol. 102, 1654 -1665), involved cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
56
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(58 citation statements)
references
References 29 publications
2
56
0
Order By: Relevance
“…Differing reports have described nuclear or cytoplasmic localization of scapinin in various transformed cell lines (1,4). Here we have shown that endogenous scapinin is present in the cytoplasm, nucleus, axon shaft, and growth cone of primary cortical neurons.…”
Section: Discussionmentioning
confidence: 68%
See 4 more Smart Citations
“…Differing reports have described nuclear or cytoplasmic localization of scapinin in various transformed cell lines (1,4). Here we have shown that endogenous scapinin is present in the cytoplasm, nucleus, axon shaft, and growth cone of primary cortical neurons.…”
Section: Discussionmentioning
confidence: 68%
“…Interestingly, three putative nuclear localization sequences have been proposed by Sagara et al (1), with the second of these located adjacent to the Ser-277 phosphorylation site ( 277 pSPKKR 281 ; putative nuclear localization sequence is underlined). The relationship between phosphorylation and this particular nuclear localization sequence is difficult to investigate directly because mutation of the proline or basic residues to disrupt the putative nuclear localization sequence would almost certainly interfere with phosphorylation by the Ser-277 kinase.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations